FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENINGKATAN PENDAPATAN PEDAGANG SESUDAH PENATAAN PASAR NGARSOPURO SOLO - Wardiningsih, Suprihatmi Sri; Susanti, Retno - (Universitas Slamet Riyadi, 2013)
Â ABSTRACT The purpose of this study was to know significant effect of the variable location of the market, value-added products to increase market share and revenue market traders Ngarsopuro Solo, after structuring the market. Market research sites in the sample Ngarsopuro Solo with 50 respondents, the sampling technique using Simple Random Sampling. Data collection using questionnaire and analysis of the data using linear regression, t test, F test, Coefficient of Determination Test. These results indicate there is significant market location variables, value-added products, and the market share of the revenue increase market traders Ngarsopuro Solo. Among the three variables most dominant market share is variable. Keywords: Location market, value added products, market share, revenue trader.